2017
DOI: 10.5194/acp-17-7567-2017
|View full text |Cite
|
Sign up to set email alerts
|

Observations of bromine monoxide transport in the Arctic sustained on aerosol particles

Abstract: The return of sunlight in the polar spring leads to the production of reactive halogen species from the surface snowpack, significantly altering the chemical composition of the Arctic near-surface atmosphere and the fate of long-range transported pollutants, including mercury. Recent work has shown the initial production of reactive bromine at the Arctic surface snowpack; however, we have limited knowledge of the vertical extent of this chemistry, as well as the lifetime and possible transport of reactive brom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 44 publications
6
64
0
Order By: Relevance
“…The BrO vmr ranges reported herein (Fig. 10) are comparable to previous tropospheric Artic studies (e.g., Tuckermann et al, 1997;Hönninger and Platt, 2002;Prados-Roman et al, 2011;Liao et al, 2012;Peterson et al, 2017;Simpson et al, 2017) and 35 consistent with the few existing Antarctic measurements (e.g., Table 1). By adding the BrO measurements provided in the frame of this work to the few previous ground-based observations performed at Antarctica from different sites, Fig.…”
Section: Vertical Profiles Of Bro In the Antarctic Tropospheresupporting
confidence: 91%
See 2 more Smart Citations
“…The BrO vmr ranges reported herein (Fig. 10) are comparable to previous tropospheric Artic studies (e.g., Tuckermann et al, 1997;Hönninger and Platt, 2002;Prados-Roman et al, 2011;Liao et al, 2012;Peterson et al, 2017;Simpson et al, 2017) and 35 consistent with the few existing Antarctic measurements (e.g., Table 1). By adding the BrO measurements provided in the frame of this work to the few previous ground-based observations performed at Antarctica from different sites, Fig.…”
Section: Vertical Profiles Of Bro In the Antarctic Tropospheresupporting
confidence: 91%
“…Note that, although the definition of the height of the boundary layer over ice and snow surfaces (e.g., Anderson and Neff, 2008) is out of the scope of this work, the BrO detection limit here provided may be regarded as an upper limit of BrO in the free troposphere since former studies place the top of the boundary layer in Antarctica between 100 m and 2 km, depending on the boundary layer parametrization and time of the year (e.g., King et al , 2006;Nygård et al, 2013). This upper limit of BrO in the free 5 troposphere of Antarctica is consistent with the few previous studies of the vertical distribution of this trace gas in the Arctic and Antarctic regions that set upper limits of BrO in the polar free troposphere of 1.5 and 2 pmol mol -1 , respectively (e.g., Frieß et al, 2011;Prados-Roman et al, 2011;Peterson et al, 2017;Hüneke et al, 2017).…”
Section: Vertical Profiles Of Bro In the Antarctic Tropospheresupporting
confidence: 89%
See 1 more Smart Citation
“…These gradient observations complement Peterson et al (2017), who used airborne DOAS to study an episode of reactive halogen transport. Here, we use these observations to study BrO spatial structures and the effects of sea-ice-lead-induced vertical mixing on reactive bromine.…”
Section: Introductionmentioning
confidence: 54%
“…4 shows time-staggered changes in BrO LT-VCD and f 200 . Peterson et al (2017) used airborne DOAS to study the 13 March case and observed a very steep BrO gradient that transports with the wind, clearly indicating that features on the edges of air masses are < 30 km. Therefore, we interpret the BrO distribution as being large regions of relatively consistent BrO on > 30 km length scales with sharp contrasts at their edges that are much smaller than satellite length scales.…”
Section: Bro Measurements Were Highly Correlated On ∼ 30 Km Length Scmentioning
confidence: 99%